Pembangunan modul m-pembelajaran Bahasa Arab di Institut Pendidikan Guru / Amani Dahaman @ Dahlan - Dahaman, Amani (2014)
This study was conducted to develop M-learning Arabic Module (M~Mu'allim) in improving the educational system of the subject Arabic Education at Teacher Education Institute (IPG), which consists of learning tutorials and ISL (Independent Self Learning) that require a form of organized and comprehensive modules. The objectives of the study are to identify the needs for M-Learning Arabic Module for learning Arabic, to design and develop the M-Learning Arabic Module (M~Mu'allim), and to evaluate the usability of M-Learning Arabic Module (M~Mu'allim) in IPGs . The course; Arabic Language Skills Teaching Methods is offered to the Bachelor of Teaching (PISMP) students at IPGs and was selected as the module’s content. The study was conducted in three phases. The objective of phase 1 is to identify the needs for an M-Learning module for learning Arabic at IPGs . The needs analysis was conducted by means of questionnaires to students and lecturers majoring in the Arabic language in the IPG. The objective phase 2 is to design and develop M-Learning Arabic Module (M~Mu'allim) for IPGs. The study applied the Delphi technique in the design module. The objective phase 3 is to evaluate the usability of the M-Learning Arabic Module (M~Mu'allim) for IPG's prospective users . Usability evaluation is based on the model of Usability Evaluation TUP (Bednarik , 2002) . The study is the Design and Development Research approach which refers to the Model Development Module Sidek (2001) to develop the modules. The study is conducted in three phases, needs analysis phase, design and development phase of the module and usability evaluations phase. All data analysis for the study of quantitative data applied Statistical Package for Social Sciences (SPSS) version 14.0. The mean and frequency analyses are used to determine whether the requirements in the design of the module M- Learning Arabic in IPG (M~Mu'allim) are in accordance with the views of students and lecturers involved. The second phase data were analyzed with the application of the median and inter quartile range. The inter quartile range was used to view the differences in each round of the expert panel and the Wilcoxon matched pairs signed-test to determine if there were significant differences between the rounds . This is to enable the interpretation of consensus for each item done. The third phase covers the usability evaluation through the qualitative analysis of the findings. The findings of qualitative usability evaluation data refer to three sections which are based on TUP model; technology, usability and learning. The findings for the first phase indicate that students and lecturers apply mobile technology hardware (100% , n=180) in their daily life . In fact, 90% of the lecturers and 73.3% of the students in IPG have internet or broadband data channels. It is concluded that the students have access to the necessary technology for mobile learning .In the context of the intended vi use of mobile technology, the results show that the mean using mobile technologies for social interaction is 4.3 (mean = 4.3) and the lowest mean value is for sharing learning materials (mean = 3.49) . These shows that consumers are less aware of the advantages of using mobile technology for shared learning and exchanging learning materials . Thus the results indicate a necessity in the development of this module with the integration of mobile technology. Also, the mean requirements of mobile computer technology in learning (mean = 4.08) is higher than the mobile phone technology (mean = 3.63). Therefore there is an indication that the students need a learning process which integrates the mobile computer technology hardware rather than the mobile phone technology. The findings of two rounds of Delphi Technique in the second phase show that the reading of the Wilcoxon test (Z) for all items is between .0000 to -.1732 , p > .05 . It indicates that there are no significant differences in responses from the expert panel between the first and the second rounds . It explains that there is consistency in the expert panel answers in the two rounds for all items. Based on the percentage of agreement (100%) and higher median value (median=4) the agreed aspects of the Delphi technique are in parallel with the items from Model Construction Module Sidek (2001) which applies the module objectives, content, strategy, logistics, media and activities. In addition, the skills and forms of assessment are to enhance and improve the M~Mu’allim module. Findings from the second phase is the production of the M~Mu’allim module. Before the module was evaluated, M~Mu’allim module’s validity and reliability were tested. Findings from the third phase of the study cover qualitative data. Findings from the interviews of lecturers and students as a whole indicate that they are satisfied with the application of M-Learning Arabic Modules (M~Mu’allim) from various aspects which are mobile technology, web usability and the learning process . The majority of lecturers and students assume that the selection of hardware mobile computing technologies is more applicable than the mobile phone hardware for learning in IPGs . There are two main implications of the results, the theoretical implications of the findings and implications of the practice . Theoretical implications of the production model is divided into m-learning modules Arabic ( M - Mu'allim ) in IPG and second , the guidelines on the process of conducting a research study module. While the implications of the practice of involving the Ministry of Education , Malaysia IPG ( IPGMs ) , IPG lecturers and students, and contributions to the field of Arabic science